Acquired von Willebrand Syndrome in IgM Monoclonal Gammopathy as the Presentation of Lymphoplasmacytic Lymphoma - Zachary Wolfe; Bradley Lash (Case Reports in Hematology)
Acquired von Willebrand syndrome (AVWS) is an increasingly recognized entity with numerous potential underlying etiologies. Most commonly implicated are lymphoproliferative, myeloproliferative, cardiovascular, and autoimmune disorders. Unlike inherited von Willebrand disease (vWD), AVWS tends to present at an older age and without a family history of vWD. Treatment is directed at the underlying etiology if one is uncovered, as well as treatment and prevention of bleeding. Here, we present a rare case of AVWS secondary to Waldenström macroglobulinemia which went unrecognized for several years but resolved promptly with treatment. The potential mechanisms of AVWS secondary to monoclonal gammopathies are discussed as well as strategies to treat and prevent bleeding in these patients.